АНАЛІЗ ПЕРСПЕКТИВ ТА ПИТАНЬ СТАЛОСТІ ВИРОБНИЦТВА РІДКИХ МОТОРНИХ БІОПАЛИВ В ЄС ТА В УКРАЇНІ - Geletukha, G.G.; Zheliezna, T.A.; Drahniev, S.V. (Institute of Engineering Thermophysics of NAS of Ukraine, 2023)
The purpose of the work is to analyse prospects for the production and use of liquid biofuels in Ukraine and to suggest relevant recommendations for the development of this direction, taking into account sustainability issues. The transition to biofuels is one of the effective measures for decarbonization of transport, which undergoes this process with difficulty in comparison with other energy sectors. According to 2020 data, the share of renewable energy sources in the gross final energy consumption in the EU’s transport sector is 10.2%. EU Directive RED II aims to increase this indicator to at least 14% in 2030, including the contribution of advanced biofuels and biogas produced from specified types of raw materials, at least to 3.5%. To be included in achieving the goals, motor biofuels must meet the sustainability criteria on land use and the requirements for reducing greenhouse gas emissions. The European Commission has the strictest approach to biofuels sustainability issues compared to the views of some European and international experts. In recent years, bioethanol has been produced only in small volumes in Ukraine, and there has been no production of biodiesel at all. Nevertheless, in the period until 2030, it is planned to significantly increase the consumption of motor biofuels, including advanced ones. Currently, the development of this direction in Ukraine is hindered by a number of barriers. It is recommended to create favourable conditions for the development of domestic production of motor biofuels. This may include a reduction in the excise tax, the abolition of compulsory tax bill for the full rate of excise duty when transporting bioethanol, the introduction of an export duty on rapeseed, and some other measures.